Ksenija Atanasijević – Аbout Language, Responsibility and Abuse of Words - Stojanović Prelević, Ivana Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper presents research on the philosophy of language by Ksenija Atanasijević, an important Serbian philosopher who lived and worked during the Balkan and World Wars. Her philosophy can be described as anthropological philosophy and applied ethics. In the publications of Atanasijević, one encounters an exploration of her perspectives on language, the interplay between language and thoughts, and the phenomenon of word misuse, among other related subjects. The author discerns a parallelism between Atanasijević’s conceptualization of language and its signification and the viewpoints espoused by contemporary philosophers of language, such as Austin, Searle, and Recanati. It is plausible to characterize Atanasijević as adhering to a pragmatist philosophy as well. The objective of the paper is to present Atanasijević’s view on human nature, society and ethics while establishing correlations with her viewpoints on language. The paper presents influences and connections with other philosophers and their respective philosophical frameworks. The paper aims to compare communication in the 21st century with communications in the last century. The emergence of disinformation, exemplified by the proliferation of fake news and the advent of a post-truth era, is attributed to the advancements in technology. The author aligns with the optimistic perspective put forth by Ksenija Atanasijević, advocating an optimistic vision for the future. In agreement with Atanasijević, the author asserts the imperative for individuals to conduct themselves ethically and engage in moral communication, emphasizing the necessity for such behavior to foster an ethical society.
Keywords: language; understanding; egoism; abuse of words; moral; ethical communication